Leveraging Telemedicine for Chronic Disease Management in Low- and Middle-Income Countries During Covid-19. Issue 1 (15th September 2020) - Hoffer-Hawlik, Michael A.; Moran, Andrew E.; Burka, Daniel; Kaur, Prabhdeep; Cai, Jun; Frieden, Thomas R.; Gupta, Reena
In response to the Covid-19 pandemic, many low- and middle-income countries (LMICs) expanded access to telemedicine to maintain essential health services. Although there has been attention to the accelerated growth of telemedicine in the United States and other high-income countries, the telemedicine revolution may have an even greater benefit in LMICs, where it could improve health care access for vulnerable and geographically remote patients. In this article, we survey the expansion of telemedicine for chronic disease management in LMICs and describe seven key steps needed to implement telemedicine in LMIC settings. Telemedicine can not only maintain essential medical care for chronic disease patients in LMICs throughout the Covid-19 pandemic, but also strengthen primary health care delivery and reduce socio-economic disparities in health care access over the long-term.